(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
Natalia Ginzburg’s (1916-1991) epistolary novel Caro Michele [1973] addresses, like several of the late works of the author, the decadence of the petty bourgeoisie and the crisis of the traditional institution of the family. We will develop the presence of melancholy in the novel linked to its critical component. We also propose to analyze the place that occupies the protagonist’s militancy and politics as an object of lost desire in the novel.